2022
DOI: 10.7759/cureus.22485
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-Orbital Mucormycosis After COVID-19 Infection in a Patient With Non-Hodgkin’s Lymphoma

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) may be succeeded by a spectrum of complications, including invasive fungal infections (IFIs). Here, we describe a case of rhino-orbital mucormycosis in a recovered coronavirus disease-19 (COVID-19) patient with underlying non-Hodgkin's lymphoma (NHL). Our patient was normotensive, non-diabetic, presenting with multiple non-healing ulcers on different parts of the body. She received high-dose glucocorticoids and antibiotics during her severe COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Baskar et al reported a case of rhino-orbital cerebral mucormycosis caused by COVID-19 infection in a non-diabetic patient [ 12 ]. Hannan et al also reported a case of COVID-19-induced mucormycosis in a non-diabetic patient diagnosed with non-Hodgkin lymphoma [ 13 ]. Mucormycosis is usually reported in patients with compromised immunity with associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baskar et al reported a case of rhino-orbital cerebral mucormycosis caused by COVID-19 infection in a non-diabetic patient [ 12 ]. Hannan et al also reported a case of COVID-19-induced mucormycosis in a non-diabetic patient diagnosed with non-Hodgkin lymphoma [ 13 ]. Mucormycosis is usually reported in patients with compromised immunity with associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Important interventions for controlling mucormycosis are early diagnosis, reversing the predisposing factors, surgical debridement of the infected tissue, and relevant therapeutic antifungal therapy [ 13 ]. COVID-19 patients have been prescribed steroids, which may suppress immunity in recovering and recovered COVID-19 patients and thereby can trigger mucormycosis infection [ 14 ].…”
Section: Discussionmentioning
confidence: 99%